NIAT BERWIRAUSAHA MAHASISWA DAN KETERHUBUNGANNYA DENGAN KECERDASAN-HADAPI-RINTANGAN - Metta Padmalia (Journal of Business & Applied Management, 2017)
Entrepreneurial Intention can be influenced by demographic factors (gender, age, work experience) and external factors, such as family background. One characteristic of an entrepreneur looked when he faces obstacles in managing the business, he is likely to survive and find a way out and not stop halfway. Individual ability to transform obstacles into opportunities is known as the Adversity Quotient (AQ/ adversity intelligence). Connectedness between adversity intelligence with the intention of entrepreneurship, as well as differences in the intentions of entrepreneurship by differences in gender, work experience and family background (family business and non-family business) are described in this study. Sampling technique used is purposive sampling of 126 students of the Ciputra University. Results showed the Sig. coefficient of Spearman’s rank correlationis 0.000 and the correlation coefficient is0.502; which means that there are significant linkages between adversity intelligence with the entrepreneurial intention. Independent sample test results show that the intention of entrepreneurship do not differ between male student with the girls. However, the intention of entrepreneurship students who have not experienced lower job than work experience. In addition, students who have a background in family business have higher entrepreneurial intention than students of non-family business.Keywords: entrepreneurial intention, adversity intelligence, family business